Effects of catalytic combustion behavior and adsorption/desorption properties on ethanol-sensing characteristics of adsorption/combustion-type gas sensors. Issue 3 (3rd July 2021) - Hyodo, Takeo; Hiura, Takeru; Nagae, Kazunori; Ueda, Taro; Shimizu, Yasuhiro
ABSTRACT: Adsorption/combustion-type gas sensors, subspecies of catalytic combustion-type gas sensors, show large dynamic responses to volatile organic compounds (VOCs) under the operation with a mode of pulsed temperature heating, because of the flash catalytic combustion of target VOCs adsorbed on the gas-sensing films. Catalytic combustion behavior of ethanol over γ-Al2 O3 powders loaded with and without 1 wt% Pt and/or 10 wt% metal oxide (MO: CeO2 or Bi2 O3 ) and their adsorption/desorption properties of ethanol (adsorption temperature: 150°C) were investigated, and then the ethanol-sensing characteristics of the sensors utilizing the gas-sensing materials (low and high temperatures under dynamic operation: 150°C and 450°C, respectively) have been discussed on the basis of the findings on both their catalytic combustion behavior and adsorption/desorption properties. Especially, the co-loading of Pt with CeO2 onto γ-Al2 O3 was the most effective in enhancing the dynamic response, because the relatively small amounts of various compounds that were adsorbed on the surface at 150°C efficiently oxidized at the initial stage of the pulse-driven heating to form CO2 . The effects of low and high temperatures under the pulse-heating operation on the ethanol-sensing properties of the sensor utilizing γ-Al2 O3 co-loaded with Pt and CeO2 were also clarified on the basis of the above findings.